Equitable Estoppel: Unpacking A Doctrine - Worthington, Sarah (Journal of Malaysian and Comparative Law, 1999)
The aim in this article is to float an idea. It is that the time has come to discard completely the motion of equitable estoppel - or, more particularly, to discard the notion that there is a ’doctrine’ of equitable estoppel. Instead, we should dig a little deeper and ask what exactly the law is doing in these ’estoppel cases’ and why it seeks fit to do it. On examination, the estoppel cases do not appear to be united by a common theme or doctrine. Rather, they seem to be discrete examples of equitable intervention into the law of obligations - interventions into the law of contract, unjust enrichment and tort. If this is true, then acknowledging it outright would simplify legal analysis and improve remedial predictability. The potential for unpacking the doctrine of equitable estoppel in this way is the focus of this article.